Comparative study between the structural and tectonic situation of the Southern Sinai and the Red Sea, Egypt, as deduced from magnetic, gravity and seismic data - EL-BOHOTY, Mohamed; BRIMICH, Ladislav; SALEH, Ahmed; SALEH, Salah (Contributions to Geophysics and Geodesy, 2012)
The present study is concerned with the analysis of magnetic gravity andseismic data for the regions of the South Sinai and the Red Sea areas aiming to evaluatethe subsurface geologic active structures. The magnetic method of prospecting gives aneffective presentation of the subsurface structures. Moreover, the wavenumber filtering iscarried out utilizing three types of filters with varying wavelengths. The application ofthese tools on the magnetic and gravity data discriminated the variable sources of specificdepth ranges for the residual and regional anomalies, as well as those limited to a certaindepth interval. Also it was found that the main tectonic trends have taken the NE–SWand NW–SE directions. A three-dimensional (3D) interpretation of the Bouguer anomalyand aeromagnetic maps of the Gulf of Suez rift and the northern part of the Red Sea riftare presented. A high-resolution 3D model constrained with the seismic results reveals apossible crustal thickness and density distribution of the north Red Sea rift between thesedimentary cover and the mantle.